1986
DOI: 10.1111/j.1748-5827.1986.tb03959.x
|View full text |Cite
|
Sign up to set email alerts
|

Pseudopregnancy in the bitch: the current view on aetiology and treatment

Abstract: The meaning of the word pseudopregnancy, as applied to the bitch, is discussed. Review of the literature shows that there is no evidence to support the theory that pseudopregnancy is caused by excess or persistent progesterone production. The condition is closely related to prolactin release from the pituitary gland, and can be treated using a prolactin inhibiting drug, bromocriptine

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
31
0

Year Published

1990
1990
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 22 publications
0
31
0
Order By: Relevance
“…Included can be nervousness, guarding an area, making a nest (66.1% of nonpregnant females), abdominal distention, mammary gland development with or without lactation (78.6%), external signs of labor, self-nursing, and guarding or carrying a stuffed toy or other object (53.6%). 3 an ovariohysterectomy within 3 months after estrus can also result in a sharp drop in progesterone and signs of pseudocyesis, including lactation, by 4 days postsurgery. Because the behaviors of pseudocyesis are typical of normal behaviors that start about the time progesterone levels decrease, it is reasonable to expect that up to 8 weeks may be needed for the changes of pseudocyesis to gradually stop.…”
Section: Female Sexual Behavior Problemsmentioning
confidence: 99%
“…Included can be nervousness, guarding an area, making a nest (66.1% of nonpregnant females), abdominal distention, mammary gland development with or without lactation (78.6%), external signs of labor, self-nursing, and guarding or carrying a stuffed toy or other object (53.6%). 3 an ovariohysterectomy within 3 months after estrus can also result in a sharp drop in progesterone and signs of pseudocyesis, including lactation, by 4 days postsurgery. Because the behaviors of pseudocyesis are typical of normal behaviors that start about the time progesterone levels decrease, it is reasonable to expect that up to 8 weeks may be needed for the changes of pseudocyesis to gradually stop.…”
Section: Female Sexual Behavior Problemsmentioning
confidence: 99%
“…The condition is usually mild and most cases recover spontaneously after a few weeks. Bitches with more severe signs can be treated with a variety of drugs, mainly reproductive steroids (Allen 1986). It has been suggested that all bitches develop pseudopregnancy but only some show signs of the condition.…”
mentioning
confidence: 99%
“…First, the owners find that an animal which was apparently clinically normal or only mildly affected before the operation has become a long-term problem. Secondly, conventional therapy for pseudopregnancy is much less efficient in such ovariectomised cases (Allen 1986) and, furthermore, the unknown processes which result in the normal spontaneous recovery in the entire animal appear not to be functional. This paper describes 32 bitches which had been ovariohysterectomised mainly for sterilisation, but, in a small number of cases, in an attempt to cure a pseudopregnancy.…”
mentioning
confidence: 99%
“…From this point of view, the inhibition of prolactin secretion has been the most efficient method of control. Most cases are treated on the request by the owner for several reasons (Allen 1986;Arbeiter et al 1988;Dumon et al 1993;Jochle et al 1989;Onclin et al 1995).…”
Section: Introductionmentioning
confidence: 99%
“…The receptors are located in luteotrophic cells, which synthesize and secrete prolactin in the anterior pituitary gland in humans and animals (Allen 1986;Arbeiter et al 1988;Braakman et al 1993;Dumon et al 1993;Johnston 1986;Jochle et al 1987). Dumon et al (1993), report that serotonin is an antagonist of metergoline, while cabergoline and bromergocryptine are the agonists of dopamine.…”
Section: Introductionmentioning
confidence: 99%